Is pre-freeze sperm preparation more advantageous than post-freeze? - Dimitra Apostolia Androni; Sophie Dodds; Mathew Tomlinson; Walid E Maalouf (Bioscientifica, 2021)
Human sperm cryopreservation is characterised to this day by sub-optimal success rates. Interestingly, a traditional approach to improving post-thaw outcome has been to integrate standard sperm preparation techniques into freezing protocols as a means of selecting sperm with the highest fertilisation potential prior to insemination. However, no consensus has been reached yet regarding the optimal timing (before or after freezing) of this selection step. Following analysis of a total of 20 human semen samples, which were divided into two aliquots prepared by density gradient centrifugation either before or after freezing, this study demonstrated higher post-thaw total (P < 0.0001), progressively motile (P = 0.005) and vital (P < 0.0001) sperm counts for frozen-prepared semen samples. The present study suggests that direct insemination with frozen-prepared sperm with minimal intervening post-thaw processing might be a more advantageous approach to current clinical practices, particularly for donor and patient intrauterine insemination programmes. Further research into cryopreservation-induced coiled sperm tail morphology is also warranted.